2018
DOI: 10.1186/s12957-018-1375-9
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the HOXA11 level in patients with lung squamous cancer and insights into potential molecular pathways via bioinformatics analysis

Abstract: BackgroundThis study was carried out to discover the underlying role that HOXA11 plays in lung squamous cancer (LUSC) and uncover the potential corresponding molecular mechanisms and functions of HOXA11-related genes.MethodsTwenty-three clinical paired LUSC and non-LUSC samples were utilized to examine the level of HOXA11 using quantitative real-time polymerase chain reaction (qRT-PCR). The clinical significance of HOXA11 was systematically analyzed based on 475 LUSC and 18 non-cancerous adjacent tissues from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 42 publications
(41 reference statements)
1
17
0
Order By: Relevance
“…However, a meta-analysis of data gathered from The Cancer Genome Atlas (TCGA) and Oncomine microarrays of 934 LUAD and 319 normal control tissues (the normal controls included tissues from healthy individuals combined with adjacent tumor samples and only 32 pairs of LUAD tissues and adjacent nontumorous tissues) revealed that HOXA11 is significantly overexpressed in LUAD tissues and that the expression level of HOXA11 is significantly higher in patients with lymphoid metastases and an advanced clinical stage, indicating the potential oncogenic role of HOXA11 in the genesis of LUAD [31]. Similar results have also been reported in lung squamous cell carcinoma (LUSC) by bioinformatics analysis [32]. Thus, the molecular mechanisms of HOXA11 in lung cancer pathogenesis mostly remain elusive and require further investigation.…”
Section: Discussionsupporting
confidence: 71%
“…However, a meta-analysis of data gathered from The Cancer Genome Atlas (TCGA) and Oncomine microarrays of 934 LUAD and 319 normal control tissues (the normal controls included tissues from healthy individuals combined with adjacent tumor samples and only 32 pairs of LUAD tissues and adjacent nontumorous tissues) revealed that HOXA11 is significantly overexpressed in LUAD tissues and that the expression level of HOXA11 is significantly higher in patients with lymphoid metastases and an advanced clinical stage, indicating the potential oncogenic role of HOXA11 in the genesis of LUAD [31]. Similar results have also been reported in lung squamous cell carcinoma (LUSC) by bioinformatics analysis [32]. Thus, the molecular mechanisms of HOXA11 in lung cancer pathogenesis mostly remain elusive and require further investigation.…”
Section: Discussionsupporting
confidence: 71%
“…We hypothesize that HoxB8 is also a metastasis promoter in pancreatic cancer. Downregulation of HoxA10, HoxA11, and HoxB13 in KPA cells is unexpected, because these Hox genes act as tumor-promoting genes in several types of cancers [59,60,61,62]. There are two possible explanations for this discrepancy.…”
Section: Novel Hox Genes In Pancreatic Tumorigenesis Identified Bymentioning
confidence: 99%
“…Overexpression of HOXA11 has been observed in ovarian cancer (28), bladder cancer (29), renal cell carcinoma (29) and lung cancer (30), while downregulation of HOXA11 has been observed in gastric cancer (31) and glioblastoma (32). In glioblastoma, overexpression of HOXA11 confers a tumor suppressive effect, reduces treatment resistance and contributes to a favorable prognosis (32).…”
Section: Discussionmentioning
confidence: 99%